An investigation of employment outcomes in South African manufacturing - Mercer, Sean (School of Economics, 2021)
The aim of this research paper is to investigate the employment outcomes in South African manufacturing between 1972 and 2016. The research employs a combination of qualitative and quantitative analysis in demonstrating how South Africa's manufacturing sector has become increasingly capital-intensive, with aggregate manufacturing employment falling by approximately 600 thousand jobs between 1982 – 2016. The investigation highlights the influence of industrial policy decisions in this outcome, creating a bias towards investment in capital-intensive manufacturing industries. This trend has continued post-1994, despite government's repeated commitment to job creation and strategic policy support for more labour-intensive industries. A further investigation of the manufacturing sector at a sub-industry level indicates that while capital-intensity has increased in capital and labour-intensive industries alike, the increase in aggregate manufacturing capital-intensity is due primarily to capital-intensive industries expanding their share of aggregate capital stock and output relative to labour-intensive industries. Consequently, South Africa's revealed comparative advantage lies, somewhat paradoxically, in capital-intensive production, contrasting the manufacturing sectors in similar comparator countries. To ensure a rigorous investigation of the aforementioned outcomes, the paper examines the common notion that South African real wages are too high to be competitive in labour-intensive production. The findings indicate that poor labour productivity is an equally important contributor to uncompetitive unit labour costs relative to competitor countries. As a means of addressing these challenges, utilizing a practical example, the paper proposes the use of special economic zones to create an environment from which labour-intensive production can thrive. It highlights the potential of targeted industrial policies, in a controlled environment to reduce the cost of labour whilst simultaneously improving productivity over time. Utilizing various instruments, for example wage subsidies, the example illustrates how such an approach is a cost-effective way of encouraging investment in labour-intensive industries, simultaneously offering a solution to more meaningful employment creation in South African manufacturing.